2017
DOI: 10.1101/174201
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Copy-number signatures and mutational processes in ovarian carcinoma

Abstract: Genomic complexity from profound copynumber aberration has prevented effective molecular stratification of ovarian and other cancers. Here we present a method for copynumber signature identification that decodes this complexity. We derived eight signatures using 117 shallow wholegenome sequenced highgrade serous ovarian cancer cases, which were validated on a further 497 cases. Mutational processes underlying the copynumber signatures were identified, including breakagefusionbridge cycles, homologous recombina… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
88
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 56 publications
(92 citation statements)
references
References 56 publications
2
88
2
Order By: Relevance
“…No data were available for region γ. As TCGA only includes ovary biopsies taken at the time of diagnosis, we used another independent data set including both spatial and temporal biopsies 6 to confirm our results. Analysis of recurrent alterations on this dataset with GISTIC (Supporting Information Methods, Section 5) confirmed that regions α and β show gain respectively in almost 74 and 85% of the samples (Supporting Information Results Section 6, Fig.…”
Section: Fmcr Of Amplification As a Feature Of Hgs-eocmentioning
confidence: 72%
See 2 more Smart Citations
“…No data were available for region γ. As TCGA only includes ovary biopsies taken at the time of diagnosis, we used another independent data set including both spatial and temporal biopsies 6 to confirm our results. Analysis of recurrent alterations on this dataset with GISTIC (Supporting Information Methods, Section 5) confirmed that regions α and β show gain respectively in almost 74 and 85% of the samples (Supporting Information Results Section 6, Fig.…”
Section: Fmcr Of Amplification As a Feature Of Hgs-eocmentioning
confidence: 72%
“…2 From the 591 samples of serous ovarian cancer in the repository, were selected samples from patients with HGS-EOC stage III and IV tumors and with copy number alteration data available (Supporting Information Methods, Section 5). The second cohort was a selection of 91 temporal and spatial biopsies with high data quality from a previously published data set 6 where segmented copy number data were available (see Supporting Information Methods, Section 5).…”
Section: In Silico Data Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…Copy number signatures can also be used to combine agents that are likely to be more effective. 20 HGSOC cell lines appear to depend on "quality control" pathways that sense and destroy damaged transcripts and proteins. Nonsense-mediated decay (NMD) is highly active in HGSOC cell lines.…”
Section: Do Ovarian Cancers Have Distinctive Metabolic Vulnerabilities?mentioning
confidence: 99%
“…Recently, we have used low-cost shallow WGS (sWGS) to identify CN signatures in the genomes of HGSC [88]. We used biopsy samples from the BriTROC-1 study (the first study of the UK Translational Research in Ovarian Cancer Consortium -detailed in [89]) of relapsed HGSC, and combined relative CN data from sWGS (mean ×0.1) and TP53 mutant allele frequency from deep tagged-amplicon sequencing [90] to generate absolute CN profiles.…”
Section: Complex Genomic Algorithms Including Sv and Cn Signaturesmentioning
confidence: 99%